Light-driven reversible charge transfers from ITO nanocrystals - Rebecchi, Luca; Rubino, Andrea; Camellini, Andrea; Kriegel, Ilka (Frontiers in Chemistry, 2023)
The combination of semiconductors and redox active molecules for light-driven energy storage systems has emerged as a powerful solution for the exploitation of solar batteries. In such contest, transparent conductive oxide (TCO) nanocrystals (NCs) demonstrated to be interesting materials thanks to the photo-induced charge accumulation enabling light harvesting and storage. The charge transfer process after light absorption, at the base of the proper use of these semiconductors, is a key step often resulting in non-reversible transformations of the chemicals involved. However, if considering the photocharging through TCO NCs not only as charge provider for the system, but potentially as part of the storage role, the reversible transformation of the redox compound represents a crucial aspect. In this paper, we explore the possible interaction of Indium Tin Oxide (ITO) NCs, and typical redox mediators commonly employed in catalytic applications with a twofold scope of enhancing or supporting the light-induced charge accumulation on the metal oxide NCs side and controlling the reversibility of the whole process. The work presented focuses on the effect of the redox properties on the doped metal oxides response, both from the stability point of view and the photodoping performance, by monitoring the changes in the optical behaviour of ITO/redox hybrid systems upon ultraviolet illumination.